Venture capital in emerging economies: a comparative study between South Africa and Poland - Ndzululeka, Pumeza (Research of GSB, 2018)
This study evaluates the venture capital sector in emerging economies with reference to the South African and Polish venture capital markets. The study focuses on the entrepreneurial, regulative and governmental factors that characterise emerging market venture capital sectors as well as the role that venture capitalists play in economic development. Emerging market venture capital characteristics, similarities and differences found from the literature review were tested in the South African venture capital market by conducting semi-structured interviews with six members of the South African Venture Capital and Private Equity Association. The findings confirm similarities between the two markets and highlight a few differences. The findings also show that South African VCs have very different experiences compared to the Asian VCs mainly due to institutionalization. In conclusion emerging market VCs sectors in Poland and South Africa are seen as having environments that are not deterrent to the growth of the venture capital sector but which with a few adjustments can spur on greater growth of the sector.